Control and Estimation of Posture During Quiet Stance Depends on Multijoint Coordination - Hsu, Wei-Li; Scholz, John P; Schoner, Gregor; Jeka, John J; Kiemel, Tim (Journal of neurophysiology, 2007)
1 Department of Physical Therapy and Biomechanics and Movement Science Program, University of Delaware, Newark, Delaware; 2 Institute für Neuroinformatik, Ruhr University, Bochum, Germany; and 3 Department of Kinesiology, University of Maryland, College Park, Maryland Submitted 26 October 2006; accepted in final form 17 February 2007 This study tested the hypotheses that all major joints along the longitudinal axis of the body are equally active during quiet standing and that their motions are coordinated to stabilize the spatial positions of the center of mass (CM) and head. Analyses of the effect of joint configuration variance on the stability of the CM and head positions were performed using the uncontrolled manifold (UCM) approach. Subjects stood quietly with arms folded across their chests for three 5-min trials each with and without vision. The UCM analysis revealed that the six joints examined were coordinated such that their combined variance had minimal effect on the CM and head positions. Removing vision led to a structuring of the resulting increased joint variance such that little of the increase affected stability of the CM and head positions. The results reveal a control strategy involving coordinated variations of most major joints to stabilize variables important to postural control during quiet stance. Address for reprint requests and other correspondence: J. P. Scholz, Dept. of Physical Therapy, Biomechanics and Movement Science Program, 307 McKinly Laboratory, University of Delaware, Newark, DE 19716 (E-mail: jpscholzatudel.edu )